Do state-level cultural competency educational mandates influence patient experience? - Mohammed Alzeen; Devdutt Upadhye; Rita DiLeo; Philip Cendoma; Kristine Hearld; Nancy Borkowski (Journal of Hospital Administration, 2026)
Objective: We examined whether state cultural competency educational mandates are associated with patient-reported Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scores. Methods: Analyzing data from 2018 and 2023 HCAHPS surveys, we compared state-level scores from 48 states and the District of Columbia (DC). Five states with cultural competency mandates (California, Connecticut, New Jersey, Oregon, Washington) were compared against five matched states and 38 remaining states with DC. Results: Paired t-tests revealed mandated states achieved significant improvements in doctor communication (p < .001), communication about medicines (p < .05), and discharge information (p < .05). Mandated states experienced significant declines in nurse communication (p < .05) and overall hospital ratings (p < .05). Matched states showed significant improvement only in discharge information (p < .05) and significant decline in overall hospital ratings (p < .05). The remaining states showed significant improvements in doctor communication (p < .001), communication about medicines (p < .001), discharge information (p < .001), willingness to recommend (p < .001), and summary star ratings (p < .05), while experiencing significant declines in nurse communication (p < .05), staff responsiveness (p < .01), and overall hospital ratings (p < .01). All groups experienced declines in overall hospital ratings. A direct between-group comparison of the change from 2018 to 2023 found no measure on which mandate states improved more than comparison states; on overall hospital rating, mandate and matched states declined more than the remaining states, and mandate and matched states did not differ from each other. Conclusions: These exploratory, associational findings do not support expanding cultural competency mandates; further research using hospital-level designs and broader outcomes is needed.